Appropriateness of utilisation among adult patients attending emergency department at district hospital - Ng, Anthony T. R.; Juni, Muhamad Hanafiah; I., Faisal (Community Health Society Malaysia, 2017)
Background: In Selangor, there had been a general increase in the numbers of patients seeking treatment at the emergency department. Inappropriate utilisation of emergency department in hospital will give rise to overcrowding, long waiting times and unnecessary usage of healthcare resources. This study aim is to determine the level of appropriateness of utilisation by patients attending to emergency department and the factors associated to it. Materials and Methods: A cross sectional study utilising systematic random sampling were carried out at the emergency department of Hospital Kuala Kubu Bharu. Self-administered questionnaire was given to respondents at the emergency department. Descriptive and analytical statistics were derived from IBM SPSS Statistics version 22.0 with a predetermined p>0.05 as significant value. Chi square and binomial logistic regression were used to determine the predictors of appropriateness of utilisation. Result: The response rate was (88.2%). The results of chi-square test indicated that there were significant association between time of presentation (p=0.005), 24-hours availability of the emergency department to respondents (p=0.014) and employment status (p=0.024). Binary logistic regression model showed that time of presentation and the 24-hour availability of an emergency department were significant predictors for appropriateness of utilisation. Conclusion: The study revealed, majority of the respondents utilised the emergency department appropriately. From the multivariate analysis it reveals that, time of presentation and 24-hours availability of the emergency department were significantly associated with appropriateness of utilisation. However further study would be needed to determine the relationship between cause and effect and the confounding factors.